Comparative analysis of methicillin-resistant Staphylococcus aureus isolated from outpatients of dermatology unit in hospitals and clinics. Issue 3 (March 2019) - Nakaminami, Hidemasa; Sugiyama, Taku; Okamura, Yuu; Hanawa, Mamiko; Abou, Masaki; Sawada, Kaori; Chiba, Yoshiyuki; Kobayashi, Yoko; Kawasaki, Satoru; Ueki, Toru; Funatsu, Sakae; Nagatani, Tetsuo; et al.
Abstract: Community-onset methicillin-resistant Staphylococcus aureus (CO-MRSA) is a causative agent of intractable skin infections. In general, clinical symptoms of hospital outpatients with skin infections are severer than those of clinic patients. Hence, molecular epidemiological features of the CO-MRSA strains from hospital outpatients are predicted to be different from those of clinic patients. Here, we conducted a comparative analysis for CO-MRSA isolates from outpatients with impetigo in hospitals and clinics located in the same district of Tokyo, Japan. Incidence of MRSA infection was higher in hospital outpatients (21.5%, 20/93 isolates) than in clinic patients (14.5%, 121/845 isolates). The resistance rate to clindamycin, which is a common topical antimicrobial agent in dermatology, in the isolates from hospital outpatients (60.0%) was higher than those from clinic patients (31.4%). Proportion of the staphylococcal cassette chromosome (SCC) mec type II, which is a representative type of hospital-acquired MRSA in Japan, in the isolates from hospital outpatients (65.0%) was significantly higher than those from clinic patients (30.6%) ( P  < 0.01). Multilocus sequence typing showed that the clonal complex 89-SCC mec type II (CC89-II) clone, which exhibits clindamycin resistance, was the most predominant (55.0%) in the isolates from hospital outpatients. On the other hand, all CC8-IV, CC121-V, and CC89-V clones accounted for 60% in clinic patients were susceptible to clindamycin. Our findings suggested that the clindamycin-resistant CC89-II CO-MRSA clone might be more related to skin infections in hospital outpatients than clinic patients.